2014
DOI: 10.1111/hae.12578
|View full text |Cite
|
Sign up to set email alerts
|

Is some better than none: are TEG and TGA profiles different in severe FVIII‐deficient patients with inhibitors?

Abstract: Severe factor VIII (FVIII)-deficient patients with and without FVIII inhibitors cannot be distinguished using FVIII levels. The FVIII assay is sensitive to detect factor levels below 1%. While severe FVIII-deficient, non-inhibitor patients have FVIII < 1%, they may retain unmeasurable residual factor activity. In contrast, inhibitor patients have a FVIII antibody that presumably fully eliminates FVIII activity. It is unknown whether thromboelastography (TEG) and thrombin generation assay (TGA) can differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…In this study, we had the opportunity to assess thrombin generation by TGA in unique samples from patients undergoing immune tolerance at one of the two dose levels, the lower of which was associated with significantly greater clinical bleeding. The TGA assay confirmed the presence of clot forming ability in haemophilia inhibitor patients, as previously shown [24,[26][27][28][29][30][31][32][33], but failed to differentiate clinical bleeding severity between haemophilia inhibitor patients undergoing low-dose and high-dose immune tolerance induction. While the TGA is recognized as a global assay of coagulation that correlates with haemophilia pheno-type better than factor VIII or IX activity [18][19][20][21], several recent studies report that the assay does not predict clinical bleeding severity or bleeding score in haemophilia patients with or without inhibitors [24,[26][27][28][29][30][31][32][33][34].…”
Section: Discussionsupporting
confidence: 57%
“…In this study, we had the opportunity to assess thrombin generation by TGA in unique samples from patients undergoing immune tolerance at one of the two dose levels, the lower of which was associated with significantly greater clinical bleeding. The TGA assay confirmed the presence of clot forming ability in haemophilia inhibitor patients, as previously shown [24,[26][27][28][29][30][31][32][33], but failed to differentiate clinical bleeding severity between haemophilia inhibitor patients undergoing low-dose and high-dose immune tolerance induction. While the TGA is recognized as a global assay of coagulation that correlates with haemophilia pheno-type better than factor VIII or IX activity [18][19][20][21], several recent studies report that the assay does not predict clinical bleeding severity or bleeding score in haemophilia patients with or without inhibitors [24,[26][27][28][29][30][31][32][33][34].…”
Section: Discussionsupporting
confidence: 57%
“…Interestingly, this work showed improvements in TEG profiles, similar to our results, more than 2 hours after rFVIIa dosing, suggesting the possible use of longer time intervals of rFVIIa dosing depending on individual clinical response. Although, recently, kaolin‐activated‐TEG has been reported as helpful in differentiating patients based on inhibitor status, other studies have questioned the value of kaolin‐activated TEG for evaluating response to treatment in patients without inhibitors . In this latter study, only r‐time correlated with levels of FVIII/FIX and no correlation between TEG profile and clinical outcome were found.…”
Section: Discussionmentioning
confidence: 57%
“…(2015) showed that while kaolin‐activated thromboelastography (TEG) was able to discriminate between non‐inhibitor and inhibitor patients, there was no difference between them pertaining to the TG capacity. A direct comparison between Salinas' and our findings is difficult, because in that study inhibitor samples were obtained not only from 15 patients but also by spiking plasma of 15 healthy controls and 14 non‐inhibitor patients with a polyclonal goat anti‐human FVIII antibody . In vitro spiking was chosen to demonstrate that any difference found was due to the inhibitors rather than to other factors .…”
Section: Discussionmentioning
confidence: 99%
“…A direct comparison between Salinas' and our findings is difficult, because in that study inhibitor samples were obtained not only from 15 patients but also by spiking plasma of 15 healthy controls and 14 non‐inhibitor patients with a polyclonal goat anti‐human FVIII antibody . In vitro spiking was chosen to demonstrate that any difference found was due to the inhibitors rather than to other factors . The TGA methods used in this and that study share the same principle, but only PPP was used by Salinas et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation